Disaster preparedness and the United Nations advance planning for disaster relief - Brown, Barbara Jean 1950- (Published for UNITAR by Pergamon Press, 1979)
Disaster Preparedness and the United Nations: Advance Planning for Disaster Relief examines the roles and relationships of programs being implemented by the United Nations in the area of disaster relief and preparedness. The study focuses on the disaster preparedness activities of the United Nations; the programs designed to improve the preparedness posture of disaster-prone developing countries; and the programs designed to improve the disaster relief capabilities of the organizations. The book also provides a brief review of the relationship between disasters and development; a description o
Includes bibliographical references and index
Keywords: Nations Unies; United Nations; Vereinte Nationen; Gestion des situations d'urgence; Secours aux victimes de catastrophes; Disaster relief; Emergency management / Planning; Secours d'urgence; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Wirtschaft; Emergency management -- Planning; Katastrophenhilfe